Peningkatan Sertifikasi Kecakapan Personel (SKP) Keamanan Bandara Internasional Soekarno Hatta - Endang Dwi Agustini (WARTA ARDHIA, 2011)
Attempts to create airport security, especially at the Soekarno-Hatta International Airport which is a gate of the Republic of Indonesia is one of the desires of all users of airport services. In an effort to realize and improve airport security must be supported by competent airport security personnel. From the results of field surveys, the number of security personnel Soekarno-Hatta International Airport are: Which already has Personnel Skills Certificates (SKP): Basic Aviation Security 214 persons, Junior Aviation Security 493 persons, Senior Aviation Security 182 persons, and Who haven’t yet Personnel Skills Certificates totaling 562 person are out sourcing. According the interviews results with Head of Security Division existing condition of security personnel at terminals 1 and 2 have been sufficient, while the existing condition of the security personnel at terminal 3 amounted to 124 people who had assessments. From the analysis and discussion in order to meet the needs of security personnel is programmed and to improve the assessments needed 248 persons, lack of security personnel at the desired terminal 3:124 persons. To increase the airport tax assessment organizers can do the addition by way of both internal and external. Internal assessment is done through a test that is taken from the power out sourcing to test, while the external through the recruitment test to provide the opportunity for applicants from outside environment. Through both ways can be realized to increase the number of assessments.